Injury Fear, Stigma, and Reporting in Professional Dancers - Amy J. Vassallo; Evangelos Pappas; Emmanuel Stamatakis; Claire E. Hiller (Elsevier, 2019)
Background: Professional dance is a physically demanding career path with a high injury prevalence, yet an ingrained culture of hiding or pushing through injuries. Developing better knowledge surrounding the cultural beliefs and behaviors related to injury reporting is critical to understand their incidence and burden. Therefore, the aim of this study was to investigate injury fear and injury reporting behaviors in professional dancers in Australia. Methods: This study utilized data collected in a cross-sectional survey of professional dancers in Australia. Descriptive analysis of injury fear and reporting stigma are presented with comparisons between subgroups (full-time versus part-time dancers; men versus women) conducted using two-sided Fisher's exact tests. Results: A total of 146 professional dancers were included. Over half (63%) of the respondents reported that they fear sustaining a dance-related injury, that they believe there is still a stigma surrounding injuries in dance (62%), and that this stigma has led to a delay in reporting or seeking care for an injury (51%). A lower proportion of part-time than full-time dancers reported that they would usually tell someone within their dance employment about an injury (35.1% vs. 59.6%, p = 0.006). Conclusion: Professional dancers are at risk of losing contracts or roles if they are injured, and therefore, it is common to dance through their occurrence. Many dancers, particularly those dancing part-time, are unwilling to tell their employers about their injuries. Action is required to improve this culture regarding injury reporting and help seeking for more effective injury understanding, prevention, and management in dance. Keywords: Behavior, Dance, Epidemiology, Injury, Reporting